Are preserved farms actively engaged in agriculture and conservation?. (May 2015) - Gottlieb, Paul D.; Schilling, Brian J.; Sullivan, Kevin; Esseks, J. Dixon; Lynch, Lori; Duke, Joshua M.
Highlights: This study evaluates investments on preserved farms in the US Northeast Investment rates range from a low of 19% for irrigation to a high of 69% for equipment Owner non-operators invest less, lifestyle farmers the same, as others in the sample Results suggest preserved farms are actively engaged in agriculture and conservation Abstract: This study addresses the question of whether farms enrolled in land preservation programs are actively engaged in agricultural or conservation activities. Data are drawn from an original survey administered to preserved farm owners in the states of New Jersey, Maryland, and Delaware in 2011. "Actively engaged" is defined as investment in conservation projects, buildings, equipment, or irrigation since the land was preserved. Affirmative answers to the survey's investment questions range from a low of 19% for irrigation to a high of 69% for equipment. Special attention was paid to differences between lifestyle farmers and small and large commercial farmers, which are classified using the USDA typology developed in 2000. Regression analysis estimates differences in investment behavior across these groups as well as farm tenure categories, controlling for farm size, program/state location, and demographic variables. Only owners who employ tenants or managers exclusively on their land were found to invest significantly less than the largest professional farmers, and they did so across all four types of investment. This study's findings support preservation goals articulated by legislators and program administrators, because (1) agricultural and land stewardship investments appear to be widespread on preserved farms, partly due to administrators' preference for larger parcels, (2) there is no evidence that "hobby farmers" are disproportionately attracted to farmland preservation programs – in fact the opposite seems to be true – while those that exist in our sample behave similarly to the largest commercial farmers, (3) although tenant farming is associated in the sample with lower rates of investment, it is less common on preserved farms than on all farms in the three study states. The matter of land tenure, highlighted in this as in other studies, has not yet become a primary focus of either farm-behavioral research or state agricultural policy.